Analysis of Human Resources Capacity for Cultural Heritage Managers in Bengkulu City - Darmi, Titi; Mujtahid, Iqbal Miftakhul; Nusantara, Bella Dian (Journal of Local Government Issues, 2023)
Cultural heritage is a regional potential asset that can contribute to economic growth, optimal management of cultural heritage is beneficial for the progress of tourism centers. Bengkulu City is one of the cities that has the potential for cultural heritage, which, if managed optimally can have an impact on the economic growth of Bengkulu City. However, the strategic allocation of human resources has not been done well. This study aims to determine how the capacity of human resources for cultural heritage managers in Bengkulu City is. The research method uses qualitative descriptive, data collection is carried out through in-depth interviews and group discussions. We analyzed six informants consisting of cultural heritage managers in the Bengkulu region assigned by the Jambi Province's Jambi Cultural Heritage Preservation Center (BPCB). Data analysis and interpreting the meaning of factual data are carried out qualitatively, and the results of the study show that the availability of human Resources (HR) both in quality and quantity has not been in accordance with the standards for developing human resources for cultural heritage. In addition, the lack of regional participation in increasing institutional capacity related to cultural heritage management has an impact on the non-optimal management of cultural heritage in the Bengkulu City.